Respiratory pathogens associated with intubated pediatric patients following hematopoietic cell transplant. Issue 4 (28th April 2020) - Gertz, Shira J.; McArthur, Jennifer; Hsing, Deyin D.; Nitu, Mara E.; Smith, Lincoln S.; Loomis, Ashley; Fitzgerald, Julie C.; Duncan, Christine N.; Mahadeo, Kris M.; Moffet, Jerelyn; Hall, Mark W.; Pinos, Emily L.; et al.
Abstract: Background: We describe organisms found in the respiratory tracts of a multicenter cohort of pediatric hematopoietic cell transplant (HCT) recipients with respiratory failure. Methods: Twelve centers contributed up to 25 pediatric allogeneic HCT recipients requiring mechanical ventilation for respiratory failure to a retrospective database. Positive respiratory pathogens and method of obtaining sample were recorded. Outcomes were assessed using Mann‐Whitney U test or chi‐squared analysis. Results: Of the 222 patients in the database, ages 1 month through 21 years, 34.6% had a positive respiratory culture. 105 pathogens were identified in 77 patients; of those, 48.6% were viral, 34.3% bacterial, 16.2% fungal, and 1% parasitic. PICU mortality with a respiratory pathogen was 68.8% compared to 54.9% for those without a respiratory pathogen ( P = .045). Those with a positive respiratory pathogen had longer PICU length of stay, 20 days (IQR 14.0, 36.8) vs 15 (IQR 6.5, 32.0), P = .002, and a longer course of mechanical ventilation, 17 days (IQR 10, 29.5) vs 8 (3, 17), P < .0001. Method of pathogen identification, type of pathogen, and the presence of multiple pathogens were not associated with changes in PICU outcomes. Conclusions: In this multicenter retrospective cohort of intubated pediatric post‐HCT patients, there was high variability in the respiratory pathogens identified. Type of pathogen and method of detection did not affect PICU mortality. The presence of any organism leads to increased PICU mortality, longer PICU stay, and increased duration of mechanical ventilation suggesting that early detection and treatment of pathogens may be beneficial in this population.